2007
DOI: 10.1080/03009480600827314
|View full text |Cite
|
Sign up to set email alerts
|

Dating early Holocene palaeoseismic event(s) in the Gulf of Bothnia, Baltic Sea

Abstract: Deformation structures in submarine Holocene sediments caused by palaeoseismicity have recently been found in the Olkiluoto area, Gulf of Bothnia, Baltic Sea, within old fracture zones of bedrock. In this study, the palaeoseismic event(s) was dated and the palaeoenvironment was characterized using palaeomagnetic, biostratigraphical and lithostratigraphical methods, thereby enhancing the reliability of the chronology. The variations in the inclination and declination of the Olkiluoto sediment core showed very g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…According to Sutinen et al (2014a), the Palojärvi, Paatsikkajoki and Kultima fault ruptures in the Palojärvi PGF complex were probably formed subglacially and soon after the deglaciation some 10 000 cal BP. In southern Finland, Hutri et al (2007) revealed disturbed sedimentary structures in a marine sequence in the Gulf of Bothnia off the (Ojala et al, 2017a). The study sites were sorted from the lowest to highest terrain roughness and from the gentlest to steepest slope, and calibrated 14C dates of landslide-buried organic matter from drilled sites are indicated with arrows ( Figure 1, Tables I and II).…”
Section: Ages Of Landslides In Relation To Fault Instability In Fennomentioning
confidence: 99%
See 1 more Smart Citation
“…According to Sutinen et al (2014a), the Palojärvi, Paatsikkajoki and Kultima fault ruptures in the Palojärvi PGF complex were probably formed subglacially and soon after the deglaciation some 10 000 cal BP. In southern Finland, Hutri et al (2007) revealed disturbed sedimentary structures in a marine sequence in the Gulf of Bothnia off the (Ojala et al, 2017a). The study sites were sorted from the lowest to highest terrain roughness and from the gentlest to steepest slope, and calibrated 14C dates of landslide-buried organic matter from drilled sites are indicated with arrows ( Figure 1, Tables I and II).…”
Section: Ages Of Landslides In Relation To Fault Instability In Fennomentioning
confidence: 99%
“…According to Sutinen et al (2014a), the Palojärvi, Paatsikkajoki and Kultima fault ruptures in the Palojärvi PGF complex were probably formed subglacially and soon after the deglaciation some 10 000 cal BP. In southern Finland, Hutri et al (2007) revealed disturbed sedimentary structures in a marine sequence in the Gulf of Bothnia off the Figure 6. An array of landslide scarp roughness (A) (mean standard deviation of 5×5 m grid) and backwall slope values (B) for the debris slide type of landslides in northern Finland (Ojala et al, 2017a).…”
Section: Ages Of Landslides In Relation To Fault Instability In Fennomentioning
confidence: 99%